Protein palmitoylation regulates extracellular vesicle production and function in sepsis. Issue 7 (5th July 2022) - Yang, Xiaoyuan; Zheng, Ethan; Chatterjee, Victor; Ma, Yonggang; Reynolds, Amanda; Villalba, Nuria; Wu, Mack H.; Yuan, Sarah Y.
Abstract: Extracellular vesicles (EVs) are bioactive membrane‐encapsulated particles generated by a series of events involving membrane budding, fission and fusion. Palmitoylation, mediated by DHHC palmitoyl acyltransferases, is a lipidation reaction that increases protein lipophilicity and membrane localization. Here, we report palmitoylation as a novel regulator of EV formation and function during sepsis. Our results showed significantly decreased circulating EVs in mice with DHHC21 functional deficiency ( Zdhhc21 dep/dep ), compared to wild‐type (WT) mice 24 h after septic injury. Furthermore, WT and Zdhhc21 dep/dep EVs displayed distinct palmitoyl‐proteomic profiles. Ingenuity pathway analysis indicated that sepsis altered several inflammation related pathways expressed in EVs, among which the most significantly activated was the complement pathway; however, this sepsis‐induced complement enrichment in EVs was greatly blunted in Zdhhc21 dep/dep EVs. Functionally, EVs isolated from WT mice with sepsis promoted neutrophil adhesion, transmigration, and neutrophil extracellular trap production; these effects were significantly attenuated by DHHC21 loss‐of‐function. Furthermore, Zdhhc21 dep/dep mice displayed reduced neutrophil infiltration in lungs and improved survival after CLP challenges. These findings indicate that blocking palmitoylation via DHHC21 functional deficiency can reduce sepsis‐stimulated production of complement‐enriched EVs and attenuates their effects on neutrophil activity.